A rare outcome of iron deficiency and pica: Rapunzel syndrome in a 5-year-old child - Ali İslek and Ersin Sayar and Aygen Yılmaz and Cem Boneval and Reha Artan (Turkish Journal of Gastroenterology, 2019)
Bezoar is defined as the accumulation of organic or nonbiological substances inside the gastrointestinal system. Trichobezoars are the most frequently detected ones and are mostly present in patients with neuropsychiatric disorders. The continuance of the trichobezoar tail-shaped extension over the duodenum and jejunum is described in Rapunzel syndrome. Both conditions are rarely reported in children. The present case submitted here is related to a 5-year-old girl referred with an abdominal mass and anemia, diagnosed with Rapunzel syndrome and developing trichobezoar due to iron deficiency and pica. Turkish Başlık: Demir eksikliği ve pikanın bir sonucu: 5 yaşındaki çocukta Rapunzel sendromu Anahtar kelimeler: Rapunzel Sendromu, demir eksikliği, pika Bezoar, organik veya biyolojik olmayan maddelerin gastrointestinal sistem içinde birikmesi olarak tanımlanır. Trikobezoarlar en sık görüleni olup sıklıkla nöropsikiyatrik bozukluğu olan kişilerde görülür. Trikobezoarın kuyruk şeklindeki uzantısının duodenum ve jejunum boyunca seyretmesi Rapunzel sendromu olarak tanımlanır. Her iki durum da çocuklarda nadirdir. Burada karında kitle ve anemi nedeni ile refere edilen, trikobezoar gelişiminden demir eksikliği ve pikanın sorumlu olduğu Rapunzel Sendromu tanısı alan 5 yaşında kız olgu sunuldu.